The promise - Davies, Nicola 1958- (Walker Books, 2014)
On a mean street in a mean, broken city, a young girl tries to snatch an old woman's bag. But the frail old woman, holding on with the strength of heroes, says the thief can't have it without giving something in return: the promise. It is the beginning of a journey that will change the thieving girl's life--and a chance to change the world, for good
Originally published: 2013
Keywords: Promises / Juvenile fiction; Acorns / Juvenile fiction; Picture books for children; Begrünung; Baumpflanzung; Diebstahl; Lebensfreude; Großstadt; Versprechen; Umweltschaden; Bilderbuch